Influences of collector DLZ on chalcopyrite and pyrite flotation - Gu, Guo-hua; Sun, Xiao-jun; Li, Jian-hua; Hu, Yue-hua (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
The interaction mechanism of collector DLZ in the flotation process of chalcopyrite and pyrite was investigated through flotation experiments, zeta potential measurements and infrared spectrum analysis. Flotation test results indicate that DLZ is the selective collector of chalcopyrite. Especially, the recovery of chalcopyrite is higher than 90% in neutral and weak alkaline systems, while the recovery of pyrite is less than 10%. When using CaO as pH regulator, at pH=7–11, the floatability of pyrite is depressed and the recovery is less than 5%. Zeta potential analysis shows that the zeta potential of chalcopyrite decreases more obviously than that of pyrite after interaction with DLZ, confirming that collector DLZ shows selectivity to chalcopyrite and pyrite. And FTIR results reveal that the flotation selectivity of collector DLZ is due to chemical absorption onto chalcopyrite surface and only physical absorption onto pyrite surface.